Specific Features of Nondestructive Testing of Polymer and Composite Materials Using Air-Coupled Ultrasonic Excitation and Laser Vibrometry; Russian Journal of Nondestructive Testing; Vol. 57, iss. 8 - Shpilnoy V. Yu. Viktor Yurjevich; Vavilov V. P. Vladimir Platonovich; Derusova D. A. Dariya Aleksandrovna; Druzhinin N. V. Nikolay Vladimirovich; Yamanovskaya A. Yu. Anastasiya Yurjevna (2021, 2021)
Title screen